Inflammatory response of human dental pulp to at-home and in-office tooth bleaching - Vaz, Maysa Magalhães; Lopes, Lawrence Gonzaga; Cardoso, Paula Carvalho; Souza, João Batista de; Batista, Aline Carvalho; Costa, Nádia Lago; Torres, Érica Miranda; Estrela, Carlos (Journal of Applied Oral Science, 2016)
Tooth bleaching is a technique of choice to obtain a harmonious smile, but bleaching agents may damage the dental pulp. Objective: This study evaluated the inflammatory responses of human dental pulp after the use of two bleaching techniques. Material and Methods: Pulp samples were collected from human third molars extracted for orthodontic reasons and divided into three groups: control - no tooth bleaching (CG) (n=7); at-home bleaching with 15% carbamide peroxide (AH) (n = 10), and in-office bleaching with 38% hydrogen peroxide (IO) (n=12). Pulps were removed and stained with hematoxylin-eosin for microscopic analysis of inflammation intensity, collagen degradation, and pulp tissue organization. Immunohistochemistry was used to detect mast cells (tryptase+), blood vessels (CD31+), and macrophages (CD68+). Chi-square, Kruskal-Wallis, and Mann Whitney tests were used for statistical analysis. The level of significance was set at p